Menaquinone biosynthesis: mutants of Escherichia coli K-12 requiring 2-succinylbenzoate. - Guest, J R (1977)
Two independent mutants of Escherichia coli K-12, selected for their inability to grow anaerobically with fumarate as the terminal electron acceptor, were shown to be deficient in menaquinone biosynthesis. In both cases, exogenously supplied 2-succinylbenzoate promoted normal anaerobic growth on a lactate plus fumarate medium. Anaerobic growth of the mutants on glucose minimal medium was impaired but could be restored to normal by adding either uracil or 2-succinylbenzoate. The addition of 2-succinylbenzoate (but not uracil) permitted the synthesis of menaquinone and demethylmenaquinone by both mutants. The menaquinone content of the parental strain grown on lactate plus fumarate was three times greater than observed after growth on glucose. Transduction studies with phage P1 showed that the two mutations are very closely linked and probably affect the same gene, menC, which is cotransducible with nalA (23%), glpT (51%), and purF (8 to 14%). The gene order nalA-nrdA-glpTA-menC-purF was indicated. The results were consistent with 2-succinylbenzoate being an intermediate in menaquinone biosynthesis and show that the gene designated menC (located at 48.65 min of the E. coli chromosome) is involved in the conversion of chorismate to 2-succinylbenzoate. It was also concluded that menaquinone is essential for electron transport to fumarate in E. coli.